Persepsi kemudahan, manfaat, dan kepercayaan dalam keputusan penggunaan OVO oleh generasi Z di Kota Surabaya - Rijkiya, Ayu Fatlia; Hayati, Cucu; Masyhuri, Mohammad Ali (Journal of Management and Digital Business, 2025)
Digital technology development drives the increasing use of e-wallets in society. Generation Z, known for its adaptability to technology, shows lower OVO application usage in Surabaya City than in other major cities. This phenomenon requires a deep understanding of factors influencing usage decisions. This study analyzes the influence of perceived ease of use, perceived usefulness, and trust on OVO application usage decisions among Generation Z in Surabaya City. The study employs a quantitative approach, with 100 respondents aged 15-24 years selected through purposive sampling. Data collection was conducted using structured questionnaires, and the data were analyzed using multiple linear regression. The results show that perceived ease of use, perceived usefulness, and trust significantly influence OVO application usage decisions both partially and simultaneously. Perceived usefulness becomes the most dominant variable in influencing usage decisions, with the largest contribution. The study concludes that increasing OVO usage among Generation Z requires strategies that emphasize ease of use, optimize perceived user benefits, and enhance trust in the security of the application service.